THE USE OF RAP MUSIC TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT THE FIRST GRADE STUDENTS OF SMPN 2 PAPALANG MAMUJU REGENCY - Dyan Elviyana Savitri; Indah Fadhillah Rahman (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The objective of this study was to to find out the extent of Rap Music improves the students’ vocabulary mastery. This study was focused on improving the students’ vocabulary in irregular verbs mastery. The research design applied in this study was a Quasi Experimental Design exactly Non-Equivalent Control Group Design covering 6 meetings for each classes (Experimental class andControlled Class). The instruments used was test. Further, the data analysis techniques involved in this study was quantitative analysis. The findings of this study showed that first grade students’ of SMPN 2 Papalang vocabulary mastery (irregular verbs) improved by the Rap Music by the increase of mean score of Experimental class that was 8.68 in the pre test and 48.89 in the post -test. It was also proved by the result of the statistical analysis indicated that the t -test values of the Rap Music in the post-test was 6.74 higher than t-table 2.021 (6.74 > 2.021). Based on the fact, H1 was accepted and H0 was rejected, the  researcher concluded that Rap Music was effective to improve students’ vocabulary mastery at the first grade students of SMPN 2 Papalang, Mamuju Regency.